Effective treatment of advanced Hodgkin lymphoma with a modified BEACOPP regimen for a patient with demyelinating hereditary motor and sensory neuropathy type 1 (HMSN1). Issue 5 (5th May 2022) - Hess, Patrick P.; Ventura Ferreira, Monica S.; Rolles, Benjamin; Kirschner, Martin; Holtbernd, Florian; Tometten, Mareike; Brümmendorf, Tim H.; Beier, Fabian
Abstract: Treatment for Hodgkin lymphoma (HL) in adults comprises substantial risk of chemotherapy‐induced peripheral neurotoxicity. Here, we describe the case of patient with Charcot–Marie–Tooth disease or HSMN1 and advanced Hodgkin lymphoma undergoing treatment with modified BEACOPP achieving complete remission without major aggravation of neurological symptoms. Abstract : Patients with Charcot–Marie–Tooth disease or HSMN1 and advanced Hodgkin lymphoma can be successfully treated with modified BEACOPP achieving complete remission without major aggravation of neurological symptoms.